Ultrafine wools: comfort and handle properties for next-to-skin knitwear and manufacturing performance. Issue 11 (July 2015) - Tester, David; McGregor, Bruce A; Staynes, Laurie
This study aimed to quantify the skin comfort and handle properties of a range of wool fabrics produced from ultrafine wool (13.7–15.1 µm) and in doing so determine if differences in fiber diameter and staple crimp frequency (5.3–7.1 crimps/cm) were important in these properties. The fabrics were evaluated using a range of subjective and objective measurement techniques, including the Wool ComfortMeter, the Wool HandleMeter and in wearer trials. This work indicated that single jersey fabrics made from ultrafine wool are approaching the limit of objective and subjective evaluation of next-to-skin comfort. The results from the Wool ComfortMeter, Wool HandleMeter and the wearer trial show that there were no significant effects that can be attributed to wool staple crimp (fiber curvature) in these ultrafine wool fabrics. The work also demonstrated a difference in the manufacturing response when knitted fabric made from wools of different fiber diameter (13.7–23.7 µm), and using yarns of the same count, resulted in a progressively higher fabric mass per unit area as mean fiber diameter was progressively reduced.